Copepods size structure in various phases of a cold-core eddy - Normalised Abundance Size Spectra (NASS) approach. (13th December 2020) - Jagadeesan, L.; Srinivas, T.N.R.; Surendra, A.; Kumar, G. Sampath; Aswindev, M.P; Joseph, Ignatious
Abstract: The present study addresses the copepods size structure in different phases of a cold-core eddy based on a 17 day time-series measurement (21st February to 8 th March 2016) from a coastal site in the western Bay of Bengal during the Spring Intermonsoon (SIM). Copepod size measured using FlowCAM and microscope was converted into biovolumes. Based on the salinity and temperature in discrete depth layers, sampling days were grouped into 3 Phases, pre-eddy (21–24 February), Core-eddy (28 February – 6 March) and transition (25–27 February and 7–8 March). The core-eddy phase was characterised as cool, less oxygenated and nutrient-rich in subsurface layers than pre-eddy and transition. Copepod abundance and total biovolume were relatively high in core-eddy phase compared to other phases. Copepods biovolumes were arranged in 15 size classes. Contribution of each size classes in total biovolume differed between the eddy phases. In total biovolume, smaller copepods (biovolume size class ≤ log2 (−3) mm −3 ) contribution was high (76.84%) in pre-eddy, but larger copepods proportion was high in core-eddy phase. Normalised Abundance Size Spectra (NASS) slope varied from −2.45 to −1.02. Similar to the taxonomic diversity, size diversity also high in core-eddy phase. Relatively flatter slope, high intercept and diversity in core-eddy phase suggest that copepods production and trophic efficiency was substantially increased. In short, copepods taxonomy and their size structure explain, pre-eddy contains the smaller coastal forms and core-eddy have a mixture of smaller coastal, larger oceanic and Oxygen Minimum Zone (OMZ) tolerant forms. Larger oceanic and OMZ tolerant forms in core-eddy phase indicate their entry through the transverse of the offshore formed cold-core eddy in the study site. Slope, intercept of NASS and size diversity captured the copepod species composition and production differences between the eddy phases in terms of abundance. This study suggests plankton size spectra and size diversity can be used as a tool to predict the plankton food web response in the varying environmental conditions. This study is the first of its kind explaining about copepods size structure and size spectrum changes with the hydrographical characteristics in Indian waters. Highlights: Copepods size structure in various phases of a core eddy was presented. Copepod abundance and total biovolume was high in core eddy compared to pre-eddy. NASS slopes are steeper in pre-eddy and relatively flatter in the core eddy. Smaller copepods contribution was high in Pre-eddy. Larger copepods proportion was relatively high in core eddy.